O ensino de probabilidade: uma proposta didática com o uso de materiais manipuláveis - ANDRADE, Erica Cristina da Silva (Universidade Federal do Tocantins, 2023)
Games and teaching materials have become important teaching tools in teaching at all levels, and concepts from different areas can be associated, including mathematics. Teaching through games provides the teacher with a contextualization that stimulates the process of understanding the content for students. For this, this work has the problem of discovering which premises are necessary for the development and use of a didactic sequence, with the use of games, for teaching and learning probability in high school? Thus, this work aims to enable the process of teaching and learning probability in High School, through the formulation of a didactic sequence with the use of manipulative materials. Through bibliographical research, we sought to establish a historical evolution of probability and investigate the use of games and manipulative materials in the teaching of mathematics. As a result, we built a didactic sequence for math classes, in order to apply concepts such as sample space, certain event, impossible, union and intersection of events and complementary event, in addition to probability calculation. The material produced in this work can be applied to other probability contents, since the game produced can be easily readjusted to other mathematics contents